Influence of Maternal Educational Instruction on Mothers' Knowledge About Neonatal Jaundice - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context:Neonatal jaundice (NNJ) is a common cause of neonatal morbidity and mortality in sub-Saharan Africa. Fundamental to its successful management is the role of mothers and/caregivers in the care of the newborn. Maternal knowledge about NNJ partly determines the extent to which this role is effectively discharged. To assess the influence of educational instruction about NNJ on recipient mothers' knowledge of and ability to detect NNJ.Settings and Design:This was a postintervention cross-sectional comparative analysis.Patients and Methods:A postintervention cross-sectional comparative study involving mothers accessing immunization services at a tertiary health care facility in northwestern Nigeria was conducted. Two hundred and thirty-nine mothers were interviewed to determine their knowledge of and ability to detect jaundice in newborns. Comparison of knowledge about jaundice was made between categories of mothers who had earlier received educational instructions on NNJ and those who did not. This study was approved by the Health Research and Ethics Committee of the Ahmadu Bello University Teaching Hospital Zaria.Statistical Analysis Used:Information obtained was entered and analyzed using SPSS version 20.Results:The majority (74.1%) of mothers received instruction and education on NNJ during pregnancy all of whom attended antenatal care (ANC) in the tertiary facility. Most respondents (91.6%) were aware of NNJ while only 73.6% gave the appropriate definition of neonatal jaundice of which 82.8% were those who received educational instruction on NNJ during ANC. The degree of knowledge on NNJ was significantly correlated positively with receiving NNJ educational instruction (P=